THE COMPARATIVE STUDY OF THE APPLICATION OF FINANCIAL ACCOUNTING STANDARDS BETWEEN SHARIA AND CONVENTIONAL INSURANCE IN INDONESIA - Asyari; Khairul Saleh L. Tobing; Syamsudin; Kumba Digdowiseiso (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Participating in insurance can help mitigate the risks that arise in life, such as the consequences of unforeseen losses on one's health or property ownership. There are two categories of insurance that are distinguished by their underlying principles: conventional insurance and sharia-compliant insurance. The fundamental concept behind the utilization of traditional insurance involves a transactional approach, necessitating compliance with a financial accounting standard known as PSAK. Hence, the objective of this study is to analyze the contrast between the implementation of financial accounting standards in sharia and conventional insurance. The employed approach is a systematic literature review that relies on scientific literature data. The data collection process involves three stages: identification, screening, and inclusion. The PSAK commonly utilized by sharia insurance companies comprises PSAK 108, 101, and 105. Moreover, the commonly employed PSAK (Indonesian Financial Accounting Standards) in the context of traditional insurance encompasses PSAK 28, 36, and 62. The application of PSAK has a significant impact on both sharia and conventional insurance by enhancing the acknowledgment and examination of an accounting report. In addition, PSAK facilitates the assessment of the effectiveness of insurance implementation in relation to the fundamental principles upon which the company is established.